Degradation of paracetamol by wet peroxide oxidation using carbon nanotubes synthesized from plastic solid waste - Sanches, Lucas Fenato (2022)
Within increased production and economic/social dependence of plastic utilization, an environmental problem has also emerged. In this scenario, plastic solid waste (PSW) recycling/management/recovery has become a problem of public concern, with a global generation estimated at 150 million tonnes per year. Materials produced from PSW can be classified as primary (performance/characteristics equivalent to virgin plastic), secondary (performance’s requirement lower than the original application), tertiary (PSW used as feedstock for the generation of chemicals and fuels), and quaternary (energy recovery via incineration) recycled materials [1]. For instance, pyrolysis of PSW has been extensively used for the thermochemical conversion of useless PSW into oil, gas, and carbon materials, thus classified as terciary recycled material.